Community Readiness for the Use of the Cash on Delivery (COD) Application Without a Marketplace Using an SPSS-based Likert Scale: Community Readiness for the Use of the Cash on Delivery (COD) Application Without a Marketplace Using an SPSS-based Likert Scale - Saputra, Renda Sandi; Salih, Yasir (Communication In Research And Publications, 2023)
This study aims to analyze the community's readiness for the Cash on Delivery (COD) without marketplace application as a payment method in online shopping transactions. Questionnaires were distributed to 30 respondents aged 18 to 25 years with various levels of education. The results of the questionnaire were analyzed using the SPSS statistical software, and the data obtained included age, gender, education level, and responses to several questions that were relevant to community readiness for COD services. The results of the analysis show that the majority of the community shows a high level of readiness for the COD application, with around 50.0% to 60.0% of respondents belonging to the ready and very ready categories. The diverse age range of respondents indicates that the COD application can reach young age groups, and the varying levels of education indicate that this application attracts interest from various walks of life. The gender of the respondents did not show a significant difference in the level of interest in COD services. Even though the majority showed high readiness, there were some respondents who showed a lower level of readiness. Therefore, a special approach is needed to provide further information and education to this group to increase their readiness to use COD services. In conclusion, the COD application has great potential to become a popular and reliable choice for users to make purchases online. However, effective marketing, education and product development efforts need to be continued to reach the full potential of COD services and provide better benefits to potential users. By focusing on good user experience, data security, and the right marketing strategy, COD applications have a chance of success in a competitive market.